A Regular Self-Assembly Micro-Nano Structure Based on Sodium Carboxymethyl Cellulose-Reduced Graphene Oxide (rGO-EDA-CMC) for Electrochemical Chiral Sensor. Issue 4 (1st January 2019) - Wang, Ruijuan; Mo, Zunli; Niu, Xiaohui; Yan, Min; Feng, Hangkong; Zhang, Hongjuan; Guo, Ruibin; Liu, Nijuan
Abstract : How to fabricate a stable and efficient systems for enantiomers discrimination has drawn enormous attention from researchers. Herein, our group presented a novel, convenient and fast electrochemical chiral sensor for chiral recognition based on a regular self-assembly micro-nano structure by sodium carboxymethyl cellulose (CMC) covalently functionalized reduced graphene oxide (rGO) with ethylenediamine (EDA) as a linker (rGO-EDA-CMC (2)), which successfully solved the agglomeration of sodium CMC. Also, the effect of preparation temperature for rGO-EDA-CMC (2) and the extent of amide formation among GO, CMC and EDA were investigated. The regular self-assembly micro-nano structure of rGO-EDA-CMC (2) with a large number of chiral microenvironments, which is meaningful for construction of electrochemical chiral sensor for enantiorecognition of Tryptophan (Trp) enantiomers based on three-point force, which exhibits excellent affinity for D-Trp by optimizing the interaction temperature, contact time and pH between Trp enantiomers and chiral interfaces. Further research drew conclusions that the percentage of D-Trp exhibits a fine linear relationship in Trp racemic mixtures. The proposed electrochemical chiral sensor is the first example to exploring a regular micro-nano structure material with sodium carboxymethyl cellulose self-assembly for electrochemical enantiorecognition of chiral compounds.